The connection between typological complexes of properties of the nervous system, temperaments, and personality types in the professions and sports - Drozdovski AK (Dove Medical Press, 2015)
Aleksandr K Drozdovski Sports Training Center for Russian Teams, Moscow, Russia Abstract: Based on experimental studies in education, professions and sports, an attempt was made to combine the following two historically disconnected research directions in the study of the natural human traits into a single coordinate system: Pavlov’s theory on the properties of the nervous system, as well as the types of higher nervous activity, and Jung’s theory on psychological types. It is noted that Pavlov’s school of thought was developed by his followers in Russia within the scientific school of differential psychophysiology, while Yung’s theory was developed through the works of well-known American researchers Myers and Keirsey. The spatial model that is presented here rests on the knowledge of the properties of the human nervous system and enables the prediction of psychological characteristics, temperament, and psychological types of individuals belonging to a wide age range. Keywords: differential psychophysiology, properties of the nervous system, typological complex of properties, psychological properties, temperament and psychological type